Transaction cost measurement for the evaluation of the regulation of live wildlife trade in South Africa - Dry, Gert C., speaker; van Hoven, Wouter, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Although South Africa has in theory, an economic comparative advantage in the production of indigenous wildlife, the ability to capitalize on this advantage was originally initiated by an incisive policy that entrusted ownership of wildlife to private landowners. Since 1991, wildlife ranchers have continued to transform marginal land into thriving operations despite a largely unreceptive policy environment. Discrepancies that exist between provincial permit-award procedures, the conservation status of many indigenous species, and the degree to which translocation can occur not only generates uncertainty; it also raises concerns amongst wildlife ranchers with regards to the cost of doing business. This status quo suggests that the current regulatory environment is not organized in such a way that transaction cost are minimized. Hence, the regulatory environment is not an efficiency-inducing administrative instrument that facilitates exchanges between economic agents. The paper addresses the latter; revewing policy-induced transaction cost associated with the live trade of wildlife species. It is argued that the implicit costs force consideration of externalities that would otherwise be ignored when market forced act in their own best interest. Results revealed significant implicit cost which confirms that the current regulatory environment is not efficient. This research not only indicates the need for legislation that is standardized across provinces, it also reveals the importance of transaction cost considerations when biodiversity or environmental policies are developed or amended.
Transaction cost measurement for the regulations of live wildlife trade in South Africa
Moderator: Wouter van Hoven
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses